Innate Immunity and Resistance to Tolerogenesis in Allotransplantation - Benichou, Gilles; Tonsho, Makoto; Tocco, Georges; Nadazdin, Ognjenka; Madsen, Joren C. (Frontiers in Immunology, 2012)
The development of immunosuppressive drugs to control adaptive immune responses has led to the success of transplantation as a therapy for end-stage organ failure. However, these agents are largely ineffective in suppressing components of the innate immune system. This distinction has gained in clinical significance as mounting evidence now indicates that innate immune responses play important roles in the acute and chronic rejection of whole organ allografts. For instance, whereas clinical interest in natural killer (NK) cells was once largely confined to the field of bone marrow transplantation, recent findings suggest that these cells can also participate in the acute rejection of cardiac allografts and prevent tolerance induction. Stimulation of Toll-like receptors (TLRs), another important component of innate immunity, by endogenous ligands released in response to ischemia/reperfusion is now known to cause an inflammatory milieu favorable to graft rejection and abrogation of tolerance. Emerging data suggest that activation of complement is linked to acute rejection and interferes with tolerance. In summary, the conventional wisdom that the innate immune system is of little importance in whole organ transplantation is no longer tenable. The addition of strategies that target TLRs, NK cells, complement and other components of the innate immune system will be necessary to eventually achieve long term tolerance to human allograft recipients.